Analysis of the Implementation of Digital Marketing Training in the Development of Sustainable Tourism Villages (Lembaran Ilmu Kependidikan, 2025)
The productivity of MSMEs in developing sustainable tourism villages is a key factor in the success of the development program in an area. Digital marketing is needed to expand the effectiveness of product sales that can reach all levels of society so that the marketed products can be widely known by consumers. This study aims to determine the implementation of the digital marketing training program. The research method used is qualitative research. This study uses an experimental research methodology. Data collection in this study uses grids and guidelines for interviews, observations and documentation that have been prepared previously. Triangulation of sources and methods used to check the validity of the data. Data analysis was carried out using the Miles and Hurberman model, namely data reduction, data presentation, and drawing conclusions. This study shows the results of the implementation of the digital marketing training program in the development of tourism villages starting from the training design process, training implementation, training evaluation and follow-up which contain elements of training. The conclusion of this study is that the implementation of the digital marketing training program has been carried out according to the training objectives by considering the training elements and training models found referring to the Kemp model.